Effects of entinostat, quisinostat, and tubastatin-A on alcohol consumption in male high ethanol consuming rats - Hauser, Sheketha R.; Ferguson, Laura B.; Liang, Tiebing; Jarvis, Erin E.; Mayfield, R. Dayne; Bell, Richard L. (Frontiers in Epigenetics and Epigenomics, 2025)
BackgroundThe interaction between genetics, epigenetics, and the environment plays a key role in the development of alcohol use disorder (AUD). Pharmacological treatments targeting histone deacetylases (HDACs) suggest that HDAC inhibitors (HDACi) may be potential pharmacotherapeutic treatments for AUD. The objective of the current study was to test the effects of different HDACi on ethanol intake in two rat lines selectively bred for high ethanol-consumption.MethodAdult naïve male high alcohol drinking line 1 (HAD1) or alcohol-preferring (P) rats were given continuous 24-h, 3-bottle, free-choice access to 15%, 30% ethanol concurrently with water for 8 weeks prior to testing entinostat (selective HDAC1i and HADC3i, 0, 1.25, 2.5, 5 mg/kg, i. p.), quisinostat (pan HADCi, 0, 0.5, 1.0, 2.0 mg/kg, i. p.), or tubastatin-A (selective HDAC6i, 0, 1.25, 2.5, 5 mg/kg, i. p.) over 4-5 consecutive days.ResultsIn HAD1 rats, entinostat reduced 2-, 4-, and 24-h ethanol intake across the 2nd – 5th test days; while, in P rats, entinostat’s effect was primarily seen at the 24-h time-point, at the highest dose and only across three test days. The high dose of quisinostat effectively reduced 24-h ethanol intake across the 1st—4th test days in HAD1 rats but was ineffective in P rats. Tubastatin-A did not alter ethanol intake in either rat line.ConclusionOverall, the results confirmed that a pan and a more selective (HDAC1 and HDAC3) HDACi effectively reduced ethanol intake in HAD1, while only the more selective HDACi reduced ethanol intake in P rats. Inhibition of HDAC6 does not appear to regulate ethanol intake in HAD1 or P rats.